Data Power in Action : Urban Data Politics in Times of Crisis - Ola Söderström; Ayona Datta (Bristol University Press, 2024)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Drawing on the study of different cities in the Global South, this book explores how the intensive use of data changes politics, power relations, and everyday life in contemporary cities. Across the volume, expert contributors show how urban actors, from the state to activists, are increasingly using data as a resource to empower their actions and support their claims, while also demonstrating how times of crisis are moments when the power of data is made visible. Focusing on the different dimensions of data power and politics in the urban realm, this is an important contribution to our understanding of how datafication transforms the places in which we live and how we experience them.